Association of Air Pollution Exposures With High-Density Lipoprotein Cholesterol and Particle Number: The Multi-Ethnic Study of Atherosclerosis. Issue 5 (May 2017) - Bell, Griffith; Mora, Samia; Greenland, Philip; Tsai, Michael; Gill, Ed; Kaufman, Joel D.
Abstract : Objective—: The relationship between air pollution and cardiovascular disease may be explained by changes in high-density lipoprotein (HDL). Approach and Results—: We examined the cross-sectional relationship between air pollution and both HDL cholesterol and HDL particle number in the MESA Air study (Multi-Ethnic Study of Atherosclerosis Air Pollution). Study participants were 6654 white, black, Hispanic, and Chinese men and women aged 45 to 84 years. We estimated individual residential ambient fine particulate pollution exposure (PM2.5 ) and black carbon concentrations using a fine-scale likelihood-based spatiotemporal model and cohort-specific monitoring. Exposure periods were averaged to 12 months, 3 months, and 2 weeks prior to examination. HDL cholesterol and HDL particle number were measured in the year 2000 using the cholesterol oxidase method and nuclear magnetic resonance spectroscopy, respectively. We used multivariable linear regression to examine the relationship between air pollution exposure and HDL measures. A 0.7×10 − 6 m − 1 higher exposure to black carbon (a marker of traffic-related pollution) averaged over a 1-year period was significantly associated with a lower HDL cholesterol (−1.68 mg/dL; 95% confidence interval, −2.86 to −0.50) and approached significance with HDL particle number (−0.55 mg/dL; 95% confidence interval, −1.13 to 0.03). In the 3-month averaging time period, a 5 μg/m 3 higher PM2.5 was associated with lower HDL particle number (−0.64 μmol/L; 95% confidence interval, −1.01 to −0.26), but not HDL cholesterol (−0.05 mg/dL; 95% confidence interval, −0.82 to 0.71). Conclusions—: These data are consistent with the hypothesis that exposure to air pollution is adversely associated with measures of HDL. Abstract : Supplemental Digital Content is available in the text.